Literature review: Combined therapy with peritoneal dialysis and hemodialysis as renal replacement therapy - Hiroaki Io; Junichiro Nakata; Hiroyuki Inoshita; Toshiki Kano; Masanori Ishizaka; Masahiro Muto; Yu Sasaki; Takuya Maeda; Haruna Fukuzaki; Yuki Shimizu; Yusuke Suzuki (Renal Replacement Therapy, 2022)
Abstract Background Peritoneal dialysis (PD) is the recommended renal replacement therapy for patients with end-stage kidney disease. Complementary hemodialysis (HD) once per week for PD patients can aid in achieving adequate dialysis and extend the duration of PD treatment. In Japan, this therapy is termed “combined therapy with PD and hemodialysis (combPDHD).” CombPDHD represents a treatment option for PD patients for whom adequate dialysis cannot be maintained. CombPDHD has been widely applied in Japanese PD patients; however, it is much less common outside of Japan. Clinical evidence, particularly regarding long-term prognosis and appropriate duration of treatment, remains insufficient. Summary CombPDHD will be required as an alternative for increasing the dose of PD under various conditions, such as a loss of residual kidney function (RKF) and peritoneal functional failure. The Japanese regimen for combPDHD involves 5 or 6 days of PD, combined with one weekly session of hemodialysis. According to some reports, the potential benefits of combPDHD are peritoneal rest with improved peritoneal function and delay in membrane deterioration. CombPDHD prevents peritoneal dysfunction and reduces cardiovascular complications by adjusting the fluid volume and improving renal anemia. Increased D/PCr indicates a deterioration in peritoneal function and is an independent risk factor for encapsulating peritoneal sclerosis (EPS). It is previously reported that no significant differences in combPDHD duration were observed between EPS and non-EPS groups. Laparoscopic findings involving patients with combPDHD revealed that there was a difference in abdominal wall degeneration depending on the intra-abdominal cavity of each case. Recently, prospective studies on long-term peritoneal function, survival, and hospitalization in combPDHD have been reported. However, reviews evaluating combPDHD long-term outcomes in multicenter and prospective studies are lacking. Conclusion It is difficult to continue PD alone with a declining RKF or when self-management is poor. Hence, combPDHD should be started to adjust the fluid volume, with adequate dialysis dose and peritoneal rest. This therapy is useful from a lifestyle viewpoint during the transition period from PD to HD and should not be continued indefinitely.